Workplace Violence against Psychiatric Nurses - Abu-Baker, Rasha; Alshdefat, Aisha (International Journal of Psychosocial Rehabilitation, 2020)
Workplace violence has become a world-wide concern. Nurses who working in psychiatry environments have a 20 times higher rate of physical violence than working in public health unit, and experience all types of patient aggression at higher rates than do medical-surgical nurses. Psychiatric nurses experiencing violence in the workplace has become a workplace safety concern to which health institutions worldwide attach considerable importance. Workplace violence is a critical factor that affects the workplace safety of nursing staff and contributes to a reduced level of efficiency and productivity in health care, has a negative impact on the nurses quality of work and job satisfaction, increased absenteeism and affect negatively on the quality of patient care. The aim of this paper is to help psychiatric nurses better understand the scope and nature of violence and to protect them from abusive patients and relatives in psychiatric setting.